Water crisis management: satisfaction level, effect and coping of the consumers - Mat Said, Aini; Ahmadun, Fakhru'l-Razi; Suan, K. Siew (Kluwer Academic Publishers, 2001)
The recent global experience of the 1998 El Nino has caused a long drought in Malaysia. The lack of rainfall in the catchment areas especially in the state of Selangor has resulted the two dams that supply water to Kuala Lumpur and surrounding regions to almost critical levels. The water crisis lasted from March to September 1998 and affected 1.8 million residents. This study was undertaken to investigate the consumers' level of satisfaction towards the strategy of the water crisis management undertaken by the state water authority. The effect of the crisis and the coping behaviour of the affected residents were also assessed. Data were collected by using interview survey on 140 residents living in one of the affected regions. It was found that on the whole the residents were only moderately satisfied with the strategy of water crisis management carried out by the state water authority. They were very unsatisfied with the quantity and quality of water provided and the distance to fetch the water from the static tanks. Majority of the respondents adopted a coping strategy by prioritizing their daily activities. The crisis had affected their work and daily activities. The positive effect of the crisis was the changing attitude of the residents in appreciation of the value of water and an increase in neighbourly spirit and relationships. Underlying causes were analyzed, ways to overcome any future water crisis were discussed and recommendations were proposed.